Welterfahrung - Selbsterfahrung: Konstitution und Verhandlung von Subjektivität in der spanischen Literatur der frühen Neuzeit - Matzat, Wolfgang; Teuber, Bernhard (Iberoromania / Beihefte, 2000)
In the last few years, inquiry into the precursor forms of modern subjectivity has proved its worth as a fruitful approach in literary studies. The articles in this volume are the products of a colloquium held in Bonn in 1998 and they regard early modern Spanish literature from this perspective. The range of authors and texts discussed extends from the very beginnings of the modern age (novela sentimental, »Celestina«) to baroque authors like Quevedo and Garcián.